2006
DOI: 10.1042/bj20051657
|View full text |Cite
|
Sign up to set email alerts
|

A novel subfamily of monomeric inorganic pyrophosphatases in photosynthetic eukaryotes

Abstract: Two sPPases (soluble inorganic pyrophosphatases, EC 3.6.1.1) have been isolated from the microalga Chlamydomonas reinhardtii. Both are monomeric proteins of organellar localization, the chloroplastic sPPase I [Cr (Ch. reinhardtii)-sPPase I, 30 kDa] is a major isoform and slightly larger protein than the mitochondrial sPPase II (Cr-sPPase II, 24 kDa). They are members of sPPase family I and are encoded by two different cDNAs, as demonstrated by peptide mass fingerprint analysis. Molecular phylogenetic analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 51 publications
0
40
0
Order By: Relevance
“…Proteins were separated by SDS-PAGE using standard procedures. Proteins were then transferred to nitrocellulose filters and probed with antibodies raised against the sPPase PPA I from the microalga Chlamydomonas reinhardtii (14) or a commercial anti-GFP antibody (Clontech, catalog number 632460). Proteins were visualized on x-ray films using horseradish peroxi-dase-coupled secondary antibodies and a chemiluminescence kit (Millipore, catalog number WBKLS0100).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins were separated by SDS-PAGE using standard procedures. Proteins were then transferred to nitrocellulose filters and probed with antibodies raised against the sPPase PPA I from the microalga Chlamydomonas reinhardtii (14) or a commercial anti-GFP antibody (Clontech, catalog number 632460). Proteins were visualized on x-ray films using horseradish peroxi-dase-coupled secondary antibodies and a chemiluminescence kit (Millipore, catalog number WBKLS0100).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, cytosolic levels of this protein have been shown to be increased in several proteomics studies dealing with cancer tissues from different origins, such as lung and colon (12,13). In addition, plants have a very intricate PP i metabolism: they possess a number of structurally and catalytically diverse PP i -utilizing proteins like the membrane-bound H ϩ -PPases, several PP i -dependent glycolytic enzymes, and multiple sPPase isoforms (2,3,14). It has been observed that photosynthetic carbon assimilation and plant metabolism in general are greatly affected by changes in the levels of soluble PPases (15)(16)(17).…”
mentioning
confidence: 99%
“…While yeast and animals possess mitochondrial PPases (Lundin et al, 1991;Curbo et al, 2006), so far no mitochondrial PPase has been identified in plants. But generally PPases remove pyrophosphate (PP i ) that is created as a byproduct of anabolic processes such as nucleic acid, protein, and carbohydrate synthesis (Gómez-García et al, 2006). Removal of PP i is necessary to prevent the inhibition of thermodynamically unfavorable reactions (Maeshima 2000).…”
mentioning
confidence: 99%
“…However, the Arabidopsis genome possesses six sPPase genes: AtPPa1 through AtPPa6, which correspond to At1g01050, At2g18230, At2g46860, At3g53620, At4g01480, and At5g09650, respectively (Meyer et al 2012, Ferjani et al 2014. These homologs are subdivided into prokaryotic (AtPPa1 to AtPPa5) and eukaryotic types (AtPPa6) (Rojas-Beltrán et al 1999, Gómez-García et al 2006. Despite being soluble, these enzymes share common features with the vacuolar H + -PPase, such as their requirement for Mg 2+ for activity.…”
Section: Ppi Homeostasis: Who Is In Charge?mentioning
confidence: 99%